2014
DOI: 10.1149/2.1021414jes
|View full text |Cite|
|
Sign up to set email alerts
|

Modeling and Experimental Validation of Electrochemical Reduction of CO2to CO in a Microfluidic Cell

Abstract: A steady-state isothermal model is presented for the electrochemical reduction of CO 2 to CO in a microfluidic flow cell. The full cell model integrates the transport of charge, mass, and momentum with electrochemistry for both the cathode and anode. Polarization curves obtained from experiments conducted at different flow rates with varying applied cell potentials are used to determine the kinetic parameters in the electrochemical reaction rate equations. The parameterized model is validated using a different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
100
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 68 publications
4
100
0
Order By: Relevance
“…The configuration shown in Fig. 10c represents a novel kind of reactor that was introduced by Kenis et al 96,97 and which is shown in Fig. 13.…”
Section: Electrochemical Reactor Configurationmentioning
confidence: 99%
“…The configuration shown in Fig. 10c represents a novel kind of reactor that was introduced by Kenis et al 96,97 and which is shown in Fig. 13.…”
Section: Electrochemical Reactor Configurationmentioning
confidence: 99%
“…Fuel crossover in the middle channel can be reasonably neglected as mixing of the two streams occurs by transverse diffusion only and is restricted to a thin interfacial region at the center of the channel [1,2]. Furthermore, the electrolyte conductivity in the middle channel is stable due to the excess supporting electrolyte [40]. The charge transport in the middle channel can be calculated without knowing the species distribution in the middle channel.…”
Section: Conservation Of Massmentioning
confidence: 99%
“…Electrofuels synthesised from renewable electricity such as wind or solar can have very low CO 2 footprint, especially when obtained from CO 2 [45][46][47][48][49]. However, in view of life cycle perspective there are some CO 2 emissions associated with renewable power generation (see Table 1) and additional CO 2 emissions are created by applying an electricity-to-electrofuel conversion step.…”
Section: Impact Of the Biogas End Use Phasementioning
confidence: 99%